Comparison of Physiologic versus Pharmacologic Mydriasis on Anterior Chamber Angle Measurements Using Spectral Domain Optical Coherence Tomography. (23rd March 2015) - Dastiridou, Anna I.; Pan, Xiaojing; Zhang, ZhouYuan; Marion, Kenneth M.; Francis, Brian A.; Sadda, Srinivas R.; Chopra, Vikas
Abstract : Purpose . To compare the effects of physiologic versus pharmacologic pupil dilation on anterior chamber angle (ACA) measurements obtained with spectral domain optical coherence tomography (SD-OCT). Methods . Forty eyes from 20 healthy, phakic individuals with open angles underwent anterior segment OCT imaging under 3 pupillary states: (1) pupil constricted under standard room lighting, (2) physiologic mydriasis in a darkened room, and (3) postpharmacologic mydriasis. Inferior angle Schwalbe's line-angle opening distance (SL-AOD) and SL-trabecular-iris-space area (SL-TISA) were computed for each eye and pupillary condition by masked, certified Reading Center graders using customized grading software. Results . SL-AOD and SL-TISA under pupillary constriction to room light were0.87 ± 0.31 mm and0.33 ± 0.14 mm 2, respectively; decreased to0.75 ± 0.29 mmP < 0.01 and0.29 ± 0.13 mm 2 P < 0.01, respectively, under physiologic mydriasis; and increased to0.90 ± 0.38 mmP < 0.01 and0.34 ± 0.17 mm 2 P = 0.06 under pharmacologic mydriasis compared to baseline. Conclusions . Using SD-OCT imaging, pharmacologic mydriasis yielded the widest angle opening, whereas physiologic mydriasis yielded the most angle narrowing in normal individuals with open iridocorneal angles. Accounting for the state of the pupil and standardizing the lighting condition would appear to be of importance for future studies of the angle.